Ethnomedicinal plant knowledge and practice of the Oromo ethnic group in southwestern Ethiopia - Yineger, Haile (BioMed Central, 2008)
An ethnomedicinal study was conducted to document the indigenous medicinal plant knowledge and use by traditional healers in southwestern Ethiopia from December 2005 to November 2006. Data were collected from 45 randomly selected traditional healers using semi-structured interviews and observations. Sixty-seven ethnomedicinal plant species used by traditional healers to manage 51 different human ailments were identified and documented. Healers' indigenous knowledge was positively correlated with their reported age but not with their educational level. High degree of consensus was observed among traditional healers in treating tumor (locally known as Tanacha), rabies (Dhukuba Seree) and insect bite (Hadhaa). The use of more than one species was significantly cited for remedy preparations. The reported abundance of the ethnomedicinal plant species varied significantly with respect to the presence of multiple uses of the reported species. Our results showed that ethnomedicinal plant species used by healers are under serious threat due to several factors, which indicates the need for urgent attention towards their conservation and sustainable utilization.